The Effectiveness of Inquiry-Based Learning Methods on Enhancing Critical Thinking Skills of Fourth Grade Students at SDN 2 Alur Dua Mas: A Literature Review - MARWIYAH MARWIYAH (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This literature review explores the effectiveness of inquiry-based learning methods in enhancing critical thinking skills among fourth-grade students at SDN 2 Alur Dua Mas. Given the rising importance of critical thinking in today’s educational landscape, this review synthesizes various studies that highlight how inquiry-based learning promotes active engagement, stimulates curiosity, and fosters independent reasoning among students. By encouraging students to ask questions, investigate topics, and discuss their findings, this approach enables them to develop essential analytical and evaluative skills. The findings indicate that students who experience inquiry-based learning demonstrate significant improvements in their critical thinking abilities compared to those taught through traditional methods. This review aims to provide insights into the potential of inquiry-based learning as an impactful teaching strategy to cultivate critical thinkers in the classroom